Como criar possibilidades de financiamento para a agricultura familiar adotando o Plano ABC Nacional? - Laurenzana, Roberto Domenico (2015)
Over the past years, through the refinement of agricultural policies, budgetary resources for family farming (Agricultura Familiar) have increased consistently, through Pronaf. The increase in the effective use of resources and ever increasing number of contracts is evident and can be seen in all regions of Brazil. The parameters of the study’ also took into consideration the importance of Family Farming in the current context, borne out internationally with Resolution 66/222 of 28.03.2012 of the General Assembly, which has given the United Nations Food and Agriculture Organization (FAO) the mandate to implement the ‘International Year of Family Farming’ (AIAF) in 2014, in partnership with the governments of member countries as well as with other international and non-governmental organizations engaged in agriculture and food safety policy. At the same time, given the growing concern about environmental issues, the ‘Sector Plan for Mitigation and Adaptation to Climate Change for the Consolidation of a Low-Carbon Economy in Agriculture’, known as the ABC Plan, is an important part of the voluntary commitment made by Brazil in 2009 at the 15th Conference of the Parties - COP15 held in Copenhagen, to reduce emissions of greenhouse gases by 2020. Part of the commitment must be met by family farms, which increases its responsibility for issues that go beyond the supply of food, raw materials and power generation etc. The ABC Program, the mechanism by which Brazilian farmers can access credit to implement low-carbon technologies is already included in the actions provided for in the Brazilian Agricultural Credit Policy, but challenges remain for the ABC Program to increase the transfer of these funds, despite the increase in operations contracted by producers in recent years. The objective was to investigate he credit lines available through Pronaf with adherence to the ABC Plan and contribute to voluntary commitments by the country to reduce emission of greenhouse gases in the agricultural sector. To achieve this goal, we carried out a review of the literature and credit lines available by public and private banks related to the ABC Program and Pronaf. We also presented a case for the city of Bragança Paulista (SP), where it was found that there is potential for use of the credit line available to the ABC Program for producers with family farming in the region. Additionally, it was also found that the use of these resources can be used for restoration of permanent preservation areas or legal reserve, important in preserving the rivers; and especially in the context and in the current discussions about the restriction of water resources that supply large cities, as it has been occurring in the metropolitan region of São Paulo. We also identified through this study that there are synergies between some credit lines Pronaf and also the Northeast Constitutional Financing Fund - FNE - SUDENE with the technologies in the Plan ABC and thus possibilities of including family farms in emissions reduction efforts in the Brazilian agriculture with the creation / incorporation of new lines of credit, such as Pronaf Eco ABC and Pronaf ABC Floresta. Additionally we identified some challenges and some suggestions of improvements to increase the use and effectiveness of the ABC Program, to promote more emphatically support of technical assistance to the producers, prioritization of actions in the Plan ABC in some regions of the country and even more emphasis in the Ministério de Desenvolvimento Agrário (MDA) for the incorporation of technologies of low carbon agriculture in the family farming segment.